Prevalence of viruses infecting cowpea in Uganda and their molecular detection - Amayo, R.; Arinaitwe, A. B.; Mukasa, S. B.; Kyamanywa, S.; Rubaihayo, P. R.; Edema, R. (African Journal of Biotechnology, 2012)
The main areas for cowpea cultivation in Uganda were surveyed in June and October 2006 for viruses affecting the crop. Seed and leaf samples from symptomatic and asymptomatic plants were collected from farmers’ fields and analysed for infecting viruses using double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA). The viruses detected in the leaf and seed samples were: cucumber mosaic cucumovirus (CMV), cowpea mild mottle calarvirus (CPMMV), cowpea mottle carmovirus (CPMoV), Cowpea chlorotic mottle bromovirus (CCMV), Cowpea yellow mosaic comovirus (CYMV), cowpea severe mosaic comovirus (CPSMV), cowpea aphid-borne mosaic potyvirus (CABMV) and Southern bean mosaic sobemovirus (SBMV). CPMV was detected only in leaf samples. CMV and CABMV were later confirmed using reverse transcription polymerase chain reaction (RT-PCR). Of the viruses detected in leaf samples, 53.26% occurred as single infections, 24.46% dual and 22.28% multiple infections. Similarly, analysis of seed samples revealed infection of 40.6, 34.6 and 24.8% for single, dual and multiple infections, respectively. Multiple virus infections were associated with more disease severity and higher yield losses. The seed transmission levels of 23.0, 20.3 and 16.4% were recorded for CMV, CPMMV and CABMV, respectively. This study identified six more viruses in addition to what was previously reported in the country, of which eight were seed-borne. This necessitates the need for the production and use of virus-free seeds, development of virus resistant genotypes and adoption of efficient seed certification systems.